The Utilization of Picture and Picture Strategy: An Effective Way to Improve EFL Students’ Writing Ability - Hakim, M. Arif Rahman; Susanti, Trinur; Asiyah, Asiyah; Abidin, Mohamad Jafre Zainol (Madania: Jurnal Kajian Keislaman, 2020)
The aim of this study is to find out whether or not there was a significant difference between students who were taught using picture and picture strategy and that of those who were not in writing recount text. The study employed a quasi-experimental study. The population in this study were the second grade students of Madrasah Tsanawiyah in Bengkulu city, Indonesia with a total number are 89 students. Out of this population, 60 students were taken as the sample. They are divided into two groups; experiement and control group, which consisted of 30 students for each group. The data were collected by using writing test. The data obtained were analyzed by using t- test formula. The data were found that the result of t-count post-test (6.34) was higher than t- table (2.00) with α = 5 % and df= 58. The finding of this research shows that there is a significant difference between students in Madrasah Tsanawiyah who are taught using picture and picture strategy and that of those who are not. Based on the result on the study, picture and picture strategy can improve students’ writing achievement in writing recount text evidently. Tujuan dari penelitian ini adalah untuk mengetahui apakah terdapat perbedaan yang signifikan antara siswa yang diajar menggunakan strategi gambar dan gambar dan siswa yang tidak dalam menulis teks pengalaman. Penelitian ini menggunakan studi quasi-eksperimental. Populasi dari penelitian ini adalah para siswa kelas dua Madrasah Tsanawiyah di kota Bengkulu, Indonesia dengan jumlah total 89 siswa. Dari populasi ini, 60 siswa diambil sebagai sampel. Mereka dibagi menjadi dua kelompok: grup eksperimen dan kontrol , yang terdiri dari 30 siswa untuk setiap kelompok. Data dikumpulkan dengan menggunakan tes menulis. Data yang diperoleh dianalisis dengan menggunakan rumus t-test. Data yang telah dihasilkan yaitu hasil dari t-hitung dari tes akhir (6,34) lebih tinggi dibandingkan t-tabel (2,00) dengan α = 5 % dan df= 58. Temuan dari penelitian ini menunjukkan bahwa terdapat perbedaan yang signifikan antara siswa di Madrasah Tsanawiyah yang diajar menggunakan strategi picture and picture dengan mereka yang tidak. Berdasarkan hasil pada penelitian, strategi picture and picture secara jelas dapat meningkatkan hasil pencapaian para siswa dalam menulis teks pengalaman.